PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT GEO INFORMATIKA SOLUSINDO KOTA BOGOR - Submission JORAPI; Gefira Dewi; Sinta Sulistiani (Journal of Research and Publication Innovation, 2024)
Employee performance is a key factor in achieving objectives and enhancing the competitiveness of a company. In this context, this research examines variables affecting employee performance, such as the work environment and motivation. This study is a quantitative research with an associative approach. Data were collected through questionnaires distributed to 60 employees of PT Geo Informatika Solusindo in Bogor City. The data collection was conducted using questionnaires developed with a Likert scale. The data analysis method employed is multiple linear regression analysis. The results of the study indicate that the t-value is greater than the t-table value (4.067 > 2.001) with a significance level of 0.000 < 0.050, which means that the work environment has a positive and significant impact on employee performance. The study also reports that the t-value is greater than the t-table value (4.496 > 2.001) with a significance level of 0.000 < 0.050, indicating that motivation has a positive and significant impact on employee performance. Furthermore, the work environment and motivation simultaneously affect employee performance. This is evidenced by the F-value being greater than the F-table value (11.702 > 3.16) with a significance level of 0.000 < 0.050. This research provides managerial implications that the work environment and motivation can influence employee performance.